Pelatihan Teamwork Pada Anggota Pengelola RPTRA Malaka Sari, Jakarta Timur - Hutahaean , Erik Saut H; Pertiwi, Yuarini Wahyu; Pohan, Hema Dayita; Perdini, Tiara Anggita; Novitasari, Farida (Lembaga Penelitian Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2022)
Child Friendly Integrated Public Space (RPTRA) is one of the communities established by the DKI Jakarta government in order to build a communication platform. RPTRA is managed by a group of individuals who have good intentions in managing it. Not only that, managers are sometimes faced with other tasks, which also require the role of all management members. As in other groups, group dynamics occur within them. For example, in the form of things throwing work responsibilities, reporting to each other, resulting in the process of working together being hampered and making the work process not smooth. The implementation of the webinar activity is carried out with the asynchronous method, in the sense that the participants and the team do not conduct the seminar on a live broadcast. But by communicating in WhatsApp groups, questions and evaluations using the g-form, delivering material through YouTube media. Through outreach activities which lasted for approximately five hours and carried out asynchronously, the counseling provided benefits for the participants.